Limited rationality and judicial cognitive biases: On the duty to judge without cognitive biases - Santa Cruz Cahuata, Julio César (2024)
This paper presents a general approach to the problem of the rationality of judicial decisions in a context of rationality limited by biases; specifically, we aim to answer the question of whether judges have the duty to judge without cognitive biases. Despite the practical importance of the issue, there are no legal provisions, or studies, that expressly resolve it. I argue that there is an institutional legal duty to design the justice system that mitigates the risk of cognitive biases in judicial decisions; but judges have a deontological duty to implement measures to manage the risk that their decisions are affected by cognitive biases. I argue, first, that the limits to human rationality do not eliminate the possibility of judges making rational legal decisions; since rationality is contextual and in the legal field it is possible to delimit the object of the decision and the relevant information, demarcating its variables; the limitations to rational judgment come mainly from the internal context, from features of human thought, among which cognitive biases stand out. Secondly, the right to be judged rationally underlies the duty of judges to judge rationally; however, it does not necessarily follow from this that judges have the duty to judge without cognitive biases, since the existence of the duty and its scope depends on additional conditions. Thirdly, the current state of the scientific and cultural context in Latin America does not allow us to uphold the legal duty of judges, considered individually, to implement measures to control cognitive biases; but it does allow us to uphold their deontological duty. The conditions do exist to affirm the state's duty of institutional design tending to control judicial biases.